JAK1/2 pathway inhibition suppresses M2 polarization and overcomes resistance of myeloma to lenalidomide by reducing TRIB1, MUC1, CD44, CXCL12, and CXCR4 expression. (18th August 2019) - Chen, Haiming; Li, Mingjie; Sanchez, Eric; Soof, Camilia M.; Bujarski, Sean; Ng, Nicole; Cao, Jasmin; Hekmati, Tara; Zahab, Brian; Nosrati, Jason D.; Wen, Mingxiang; Wang, Cathy S.; et al.
Summary: Monocytes polarize into pro‐inflammatory macrophage‐1 (M1) or alternative macrophage‐2 (M2) states with distinct phenotypes and physiological functions. M2 cells promote tumour growth and metastasis whereas M1 macrophages show anti‐tumour effects. We found that M2 cells were increased whereas M1 cells were decreased in bone marrow (BM) from multiple myeloma (MM) patients with progressive disease (PD) compared to those in complete remission (CR). Gene expression of Tribbles homolog 1 ( TRIB1) protein kinase, an inducer of M2 polarization, was increased in BM from MM patients with PD compared to those in CR. Ruxolitinib (RUX) is an inhibitor of the Janus kinase family of protein tyrosine kinases (JAKs) and is effective for treating patients with myeloproliferative disorders. RUX markedly reduces both M2 polarization and TRIB1 gene expression in MM both in vitro and in vivo in human MM xenografts in severe combined immunodeficient mice. RUX also downregulates the expression of CXCL12, CXCR4, MUC1, and CD44 in MM cells and monocytes co‐cultured with MM tumour cells; overexpression of these genes is associated with resistance of MM cells to the immunomodulatory agent lenalidomide. These results provide the rationale for evaluation of JAK inhibitors, including MM BM in combination with lenalidomide, for the treatment of MM patients.